NILAI FILOSOFIS KEADILAN DALAM EKONOMI SYARIAH - Binti Mutafarida (Program Studi Ekonomi Syariah Fakultas Ekonomi dan Bisnis Islam IAIN Kediri, 2019)
The concept of justice in Islam is different from the concept of justice in islamicteachings. Teaching justice in various aspects of life, justice does not mean thesame between one person with another, between one group with another group or between one region to another.In Islamic concept, justice means everyone gets based on their rights. In Al Quran verses also explain about justice concept, either justice in distribution matters, consumption or others. In Economics, justice also has to establish that including eliminating inequality in income. The principle of justice in Islamic economic system is contrary to the capitalist concept which develops the trickle-down effect principle, besides the characteristic of the capitalist economy is private ownership. Whereas in Islam the principles of justice enforcement are ukhuwah (brotherhood), mahabbah (mutual love), takaful (help each other) and ta'awun (mutual help). In Islam the ultimate goal of the concept of justice is welfare (falah) and not the accumulation of wealth.